From the mythical to the human. Yanantin and masintin in the Andean testimony - Larrú Salazar, Manuel (2022)
In this research, we intend to study how couple relationships are in the Quechua testimony. We can assure that, in the Quechua cosmovision, the relationships between animals, gods, men and nature are expressed indualities, by correspondence, by symmetry, by analogy, by complementarity and by reciprocity. It is a type of cognitive structure that includes the entire cosmological order. For this reason, it is possible to find traditional communities where there are roles played by both men and women that can be traced back through chronicles and Inca mythology. Consider the mythical couple Manco Capac and Mama Ocllo. The spaces they founded represent the high (hanan), the masculine (the Inca), the low (hurin) and the feminine (the Coya). In the cosmological drawing of Santa Cruz Pachacuti, this dualism is also expressed in mythical figures represented by the notions of yanantin and masintin. In the same dimension, we also mention some couples from The Huarochirí Manuscript, such as Kavillaca and Cuniraya or Chuquisuso and Pariacaca, whose performances imply a type of complementation, analogy and symmetry, aspects that will guide the analysis when we focus on the social relations between men and women in the Quechua testimony